Nonparametric Demand Analysis of U.K. Personal Sector Decisions on Consumption, Leisure, and Monetary Assets: A Reappraisal - Drake, Leigh (The Review of Economics and Statistics, 1997)
This paper utilizes a new data set to test for utility maximizing behavior and weakly separable subutility functions in the context of a utility function comprising durables, nondurables, services, leisure, and monetary asset holdings for the U.K. personal sector. All the data sets analyzed demonstrated consistency with respect to utility maximizing behavior. The weak separability results prove to be relatively invariant to the degree of aggregation over goods but highly sensitive to the assump-tion made regarding the representative consumer. Per-household scaling of the data produced a utility function that is weakly separable in goods, services and leisure, and in monetary assets.